Structural, electronic, and magnetic behaviors of 5d transition metal atom substituted divacancy graphene: A first-principles study *Project supported by the National Natural Science Foundation of China (Grant Nos. 51522601 and 51421063) and the Program for New Century Excellent Talents in University, China (Grant No. NCET-13-0173). (May 2017) - Rafique, Muhammad; Shuai 帅, Yong 永; Tan, He-ping; Hassan, Muhammad
Abstract : Structural, electronic, and magnetic behaviors of 5d transition metal (TM) atom substituted divacancy (DV) graphene are investigated using first-principles calculations. Different 5d TM atoms (Hf, Ta, W, Re, Os, Ir, and Pt) are embedded in graphene, these impurity atoms replace 2 carbon atoms in the graphene sheet. It is revealed that the charge transfer occurs from 5d TM atoms to the graphene layer. Hf, Ta, and W substituted graphene structures exhibit a finite band gap at high symmetric K -point in their spin up and spin down channels with 0.783 μ B, 1.65 μ B, and 1.78 μ B magnetic moments, respectively. Ir and Pt substituted graphene structures display indirect band gap semiconductor behavior. Interestingly, Os substituted graphene shows direct band gap semiconductor behavior having a band gap of approximately 0.4 eV in their spin up channel with 1.5 μ B magnetic moment. Through density of states (DOS) analysis, we can predict that d orbitals of 5d TM atoms could be responsible for introducing ferromagnetism in the graphene layer. We believe that our obtained results provide a new route for potential applications of dilute magnetic semiconductors and half-metals in spintronic devices by employing 5d transition metal atom-doped graphene complexes.